MDA Explained: The Model Driven Architecture™: Practice and Promise - Kleppe, Anneke (Addison Wesley, 2011)
"Jos Warmer's work has contributed greatly to the semantics of the UML. From that perspective, and in this book, he offers insight on how one can and can't use the UML to move to the next level of abstraction in building systems." —Grady Booch